2005
DOI: 10.1073/pnas.0503407102
|View full text |Cite
|
Sign up to set email alerts
|

Real-time imaging of type III secretion: Salmonella SipA injection into host cells

Abstract: Many pathogenic and symbiotic Gram-negative bacteria employ type III secretion systems to inject ''effector'' proteins into eukaryotic host cells. These effectors manipulate signaling pathways to initiate symbiosis or disease. By using time-lapse microscopy, we have imaged delivery of the Salmonella type III effector protein SipA͞SspA into animal cells in real time. SipA delivery mostly began 10 -90 sec after docking and proceeded for 100 -600 sec until the bacterial SipA pool (6 ؎ 3 ؋ 10 3 molecules) was exha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
203
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(209 citation statements)
references
References 31 publications
(21 reference statements)
6
203
0
Order By: Relevance
“…This observation was further strengthened by the results of Salmonella binding assays, in which a significant increase in the number of bacteria per infected cell was observed in cells pre‐exposed to arsenite or anisomycin, compared to control cells (Fig 5D and E, and Appendix Fig S3A). To confirm that this phenotype was related to bacterial binding, we used an invasion‐deficient but binding proficient Salmonella mutant strain ( Salmonella Δ4), which lacks four effector proteins (SopE, SopE2, SopA, and SipB) essential for invasion (Schlumberger et al , 2005; Lara‐Tejero & Galan, 2009; Misselwitz et al , 2011b). Similar to WT Salmonella , in conditions of cellular stress the Δ4 mutant strain infected a lower number of cells than in the absence of stress, but also accumulated in specific sites, resulting in a higher number of bacteria per infected cell (Fig 5D and F, and Appendix Fig S3A).…”
Section: Resultsmentioning
confidence: 99%
“…This observation was further strengthened by the results of Salmonella binding assays, in which a significant increase in the number of bacteria per infected cell was observed in cells pre‐exposed to arsenite or anisomycin, compared to control cells (Fig 5D and E, and Appendix Fig S3A). To confirm that this phenotype was related to bacterial binding, we used an invasion‐deficient but binding proficient Salmonella mutant strain ( Salmonella Δ4), which lacks four effector proteins (SopE, SopE2, SopA, and SipB) essential for invasion (Schlumberger et al , 2005; Lara‐Tejero & Galan, 2009; Misselwitz et al , 2011b). Similar to WT Salmonella , in conditions of cellular stress the Δ4 mutant strain infected a lower number of cells than in the absence of stress, but also accumulated in specific sites, resulting in a higher number of bacteria per infected cell (Fig 5D and F, and Appendix Fig S3A).…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding, considering Salmonella and Shigella, no surface-localized effector proteins have yet been found, and the few studies that have assayed effector proteins in these pathogens have indicated that these proteins are present in the cytoplasm of the bacteria before contact with target cells (15,38,39). In an investigation of S. typhimurium, Schlumberger et al (15) performed real-time imaging of SipA translocation and showed that 26% of the bacterial cells contained detectable amounts of SipA in their cytosol before they came in contact with host cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Yop effectors, in turn, are believed to be transferred into the host-cell cytoplasm through this pore during the translocation step (13). Investigators using different methods have previously demonstrated the occurrence of polarized, T3SS-dependent translocation of proteins into target cells (2,(14)(15)(16), but the detailed mechanisms underlying that process are still largely unknown.…”
mentioning
confidence: 99%
“…Bacterial invasion and co-localization with LAMP-1 was quantified by evaluating 100 randomly selected macrophages. Intracellular IpaB was stained after permeabilization of the bacteria with lysozyme as described by Schlumberger et al (2005).…”
Section: Methodsmentioning
confidence: 99%
“…During cell-to-cell spread the contact with the protrusion membrane likely triggers type III secretion. By contrast, the factor triggering type III secretion in the macrophage cytoplasm is currently unknown.Type III secretion by S. flexneri (Enninga et al, 2005) and Salmonella enterica serovar Typhimurium (Schlumberger et al, 2005) was recently analysed on a single-cell level in real time using time-lapse fluorescence microscopy. In these studies, the depletion of tetracysteine-tagged S. flexneri effectors (IpaB, IpaC) labelled with a fluoresceinconjugated biarsenical dye was analysed, or the depletion of Sal.…”
mentioning
confidence: 99%